Type I Interferons in the Treatment of Pancreatic Cancer: Mechanisms of Action and Role of Related Receptors - Vitale, Giovanni (2007)
OBJECTIVE: We evaluated the role of type I interferons (IFNs) and IFN receptors in the regulation of cell growth in 3 human pancreatic adenocarcinoma cell lines (BxPC-3, MiaPaCa-2, and Panc-1). BACKGROUND: Chemotherapy and radiotherapy have a marginal role in the management of pancreatic adenocarcinoma. The addition of IFN-α showed promising results in early clinical trials. METHODS: Cell proliferation and apoptosis were evaluated by DNA measurement and DNA fragmentation, respectively. Type I IFN receptor (IFNAR-1 and IFNAR-2 subunits) was determined by quantitative RT-PCR and immunocytochemistry. Cell cycle distribution was evaluated by propidium iodide staining and flow-cytometric analysis. RESULTS: The incubation with IFN-β for 6 days showed a potent inhibitory effect on the proliferation of BxPC-3 (IC(50), 14 IU/mL) and MiaPaCa-2 (IC(50), 64 IU/mL). The inhibitory effect of IFN-β was stronger than IFN-α in all 3 cell lines and mainly modulated by the stimulation of apoptosis, although cell cycle arrest was induced as well. The expression of the type I IFN receptors was significantly higher in BxPC-3 (the most sensitive cell line to IFN) and mainly localized on the membrane, whereas in Panc-1 (the most resistant cell line) about 60% to 70% of cells were negative for IFNAR-2c with a mainly cytoplasmic staining for IFNAR-2c. CONCLUSION: The antitumor activity of IFN-β is more potent than IFN-α in pancreatic cancer cell lines through the induction of apoptosis. Further studies should investigate in vivo whether the intensity and distribution of IFNAR-1 and IFNAR-2c may predict the response to therapy with IFN-α and IFN-β in pancreatic cancer.